Enhancing Safety in Epilepsy Surgery (EASINESS): Study Protocol for a Retrospective, Multicenter, Open Registry - Drexler, Richard; Ben-Haim, Sharona; Bien, Christian G.; Borger, Valeri; Cardinale, Francesco; Carpentier, Alexandre; Cendes, Fernando; Chandra, Sarat; Clusmann, Hans; Colon, Albert; Curtis, Marco de; Delev, Daniel; et al. (Frontiers in Neurology, 2021)
Optimizing patient safety and quality improvement is increasingly important in surgery. Benchmarks and clinical quality registries are being developed with the aim of assessing best achievable results for several surgical procedures and reduce unwarranted variation between different centers. However, there is no clinical database from international centers for establishing standardized reference values of patients undergoing surgery for mesial temporal lobe epilepsy. Design: The Enhancing Safety in Epilepsy Surgery (EASINESS) study is a retrospectively conducted, multicenter, open registry. All patients undergoing mesial temporal lobe epilepsy surgery in participating centers between January 2015 and December 2019 are included in this study. Patient characteristics, preoperative diagnostic tools, surgical data, postoperative complications, and long-term seizure outcome are recorded. Outcomes: Collected data will be used for establishing standardized reference values (“benchmarks”) for this type of surgical procedure. Primary endpoints include seizure outcome according to the International League Against Epilepsy (ILAE) classification and defined postoperative complications. Discussion: The EASINESS will define robust and standardized outcome references after amygdalohippocampectomy for temporal lobe epilepsy. After successful definition of benchmarks from an international cohort of renowned centers, these data will serve as reference values for the evaluation of novel surgical techniques and comparisons among centers for future clinical trials. Clinical trial registration: This study is indexed at clinicaltrials.gov (NT 04952298).